Description of Oxygen Saturation in Respiratory Distress Syndrome (RDS) Infants Attached to CPAP with Knee Chest Position - Eka Wahyuni; Deswita Deswita; Ira Mulya Sari (GLOBAL HEALTH SCIENCE GROUP, 2024)
Respiratory Distress Syndrome (RDS) is one of the main causes of neonatal morbidity and mortality, especially in premature infants. Interventional approaches such as Continuous Positive Airway Pressure (CPAP) with the knee-chest position are considered effective for improving oxygen saturation. However, research on the effect of this position on infants with RDS in Indonesia is still limited. This study aims to describe oxygen saturation in infants with respiratory distress syndrome (RDS) who use CPAP with the knee-chest position at Pariaman Regional Hospital. This study is a quantitative study with a cross-sectional design. The population consisted of all infants with RDS who used CPAP in the NICU room at Pariaman Hospital. A total of 15 infants were selected as samples using purposive sampling technique. Data collection was done with a questionnaire to record respondent characteristics (gender, gestational age, birth weight, type of delivery) and an observation sheet to measure oxygen saturation. Data analysis was performed using statistical software with descriptive tests, including frequency distributions and percentages. The majority of infants (66.7%) were male, with a gestational age of 34-37 weeks (80%), birth weight of 1500-2499 grams (66.7%), and delivered by caesarean section (66.7%). Oxygen saturation increased significantly after knee-chest positioning, from a mean of 94.40% before intervention on the first day to 98.73% after intervention on the third day. Statistical analysis showed that the change in oxygen saturation value was statistically significant (p<0.05). The knee-chest position effectively improves oxygen saturation in infants with RDS using CPAP. This intervention can be recommended as part of the neonatal nursing care protocol to improve oxygenation quality and support infant recovery.